Fruits, fish and the introduction of pottery in the Eastern European plain: Lipid residue analysis of ceramic vessels from Zamostje 2. (10th March 2020) - Bondetti, Manon; Scott, Sofia Chirkova; Lucquin, Alexandre; Meadows, John; Lozovskaya, Olga; Dolbunova, Ekaterina; Jordan, Peter; Craig, Oliver E.
Abstract: The Neolithization of Northern Eurasia is marked by the emergence of pottery among hunter-gatherer societies. The driving forces behind the adoption of ceramic cooking vessels among non-agricultural societies remain unclear, although previous research, mainly in North East Asia (e.g. Japan, Korea and the Russian Far East), suggests that it was adopted as a specialist technology for processing aquatic resources, linked to the intensification of fishing activities and a move to sedentism. The stratified site of Zamostje 2 in the forest zone of the Volga-Oka region includes both aceramic Mesolithic and two early ceramic horizons dating to Early Neolithic (EN) and Middle Neolithic (MN). This provides a unique opportunity to look at the impacts of the adoption of pottery on the wider economy and determine whether pottery function changes over time. This was achieved through the analysis of lipids from 166 potsherds dating from the earliest phases (mid-6th millennium cal BC) to the MN (5th millennium cal BC). Contrary to our expectations, the pottery from the EN phase was used to process a broad range of foodstuffs including terrestrial resources, such as forest fruits, in addition to freshwater fish. In contrast, pottery from the MN phase was used exclusively for processing aquatic resources. The results show that in this case, pottery was adopted as a more general-purpose cooking container, at least in the earliest phases of use, and that a specialist function only emerged later.